EXISTENTIALIST FEMINISM OF “WOMEN’S SITUATION” IN PARK JOON-HWA’S BECAUSE THIS IS MY FIRST LIFE - Silani, Putri Anifa Surya (LINGUA LITERA : journal of english linguistics and literature, 2023)
Abstract Existentialist feminism is the idea of women being able to express themselves freely in both personal and social activities without being haunted by their existence as women. This can be seen in one of Simone de Beauvoir's concepts, "women’s situations" which refers to the conditions, situations, and experiences of women in a particular society or culture. This research uses feminist theory by Simone de Beauvoir with the concept of Women's Situations. This concept is used to solve the first problem; a representation of “women’s situations” in the 21st century and the second issue; the women’s movement in dealing with the situation of women. The results of this research can be seen through a description of the "women's situation" faced by women in the 21st century, such as the challenges of married women and women in professional work environments. In addition, this research also points to the women's movement which tries to be authentic by maintaining its existence in accordance with its values and beliefs to get out of the "women's situations".